PENGEMBANGAN MODUL FISIKA MATERI GELOMBANG BUNYI BERBASIS ALAT MUSIK TRADISIONAL GONG DAN TAMBUR SABU RAIJUA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Yanesia Ratu Hegi; Jannes Bastian Selly; Markus Simeon K. Maubuthy; Hartoyo Yudhawardana (PendIPA Journal of Science Education, 2026)
This study aims to develop a physics module on sound waves based on traditional musical instruments, namely the gong and tambur of Sabu Raijua, to improve students’ critical thinking skills. This research is a type of Research and Development (R&D) using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of the study were students of class XI H at SMA Negeri 1 Hawu Mehara. The instruments used included expert validation sheets, response questionnaires, and critical thinking tests. The results showed that the module is highly valid, with a material expert score of 91% and a media expert score of 85%. It is also highly practical, as indicated by small group testing at 95%, large group testing at 93%, and teacher responses at 97%. Furthermore, the module is effective in improving students’ critical thinking skills, with an N-gain score of 0.8, categorized as high.